2005
DOI: 10.1038/sj.leu.2403876
|View full text |Cite
|
Sign up to set email alerts
|

Having a higher blast percentage in circulation than bone marrow: clinical implications in myelodysplastic syndrome and acute lymphoid and myeloid leukemias

Abstract: Determining the percentage of peripheral blood (PB) and bone marrow (BM) blasts is important for diagnosing and classifying acute myeloid leukemia (AML) and myelodysplastic syndromes (MDS). Although most patients with acute leukemia or MDS have a higher percentage of BM blasts than PB blasts, the relative proportion is reversed in some patients. We explored the clinical relevance of this phenomenon in MDS (n ¼ 446), AML (n ¼ 1314), and acute lymphoblastic leukemia (ALL) (n ¼ 385). Among patients with MDS or AL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
18
1
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 13 publications
4
18
1
1
Order By: Relevance
“…Similarly, Bcl2 has been reported as independent predictive factor of survival by Campos et al [23], independent prognostic factor for achieving complete remission by Lauria et al [16] and independent prognostic factor for reduced OS and EFS by Kornblau et al [20]. Our findings are consistent with studies by Chang et al [30] and Meshinchi et al [31] demonstrating WBC count as significant prognostic factor while blast count was demonstrated to be of prognostic significance for reduced OS by Amin et al [32]. Also, in multivariate analysis, the subgroup of Bcl2+/FLT3 protein+ emerged as significant prognostic factor followed by high WBC count for predicting poor DFS.…”
Section: Discussionsupporting
confidence: 83%
“…Similarly, Bcl2 has been reported as independent predictive factor of survival by Campos et al [23], independent prognostic factor for achieving complete remission by Lauria et al [16] and independent prognostic factor for reduced OS and EFS by Kornblau et al [20]. Our findings are consistent with studies by Chang et al [30] and Meshinchi et al [31] demonstrating WBC count as significant prognostic factor while blast count was demonstrated to be of prognostic significance for reduced OS by Amin et al [32]. Also, in multivariate analysis, the subgroup of Bcl2+/FLT3 protein+ emerged as significant prognostic factor followed by high WBC count for predicting poor DFS.…”
Section: Discussionsupporting
confidence: 83%
“…These findings are consistent with studies which demonstrated WBC count as significant prognostic factor in AML [60][61] while blast count was demonstrated to be of prognostic significance for reduced OS in AML patients as shown by Amin et al [62].…”
supporting
confidence: 82%
“…However, in contrast to MDS [21][22][23] survival of AEL patients in our series was not related to bone marrow or peripheral blood blast counts or to the number of dysplastic lineages. The number of cytopenias in AEL patients did significantly correlate with survival, as patients with a single cytopenia had a better survival (P ϭ .049) than patients with 2 or 3 cytopenias.…”
Section: Discussioncontrasting
confidence: 39%